Enraizamento de estacas de cultivares de oliveira em diferentes tempos de imersão em AIB - Inocente, Verena Heloise Hanel (2016)
The vegetative propagation by cutting is the most commonly used method in olive trees multiplication and the technical viability of this method depends on the capacity of the vegetal material used to make rooting and the rooting quality grown. The results may vary according to the regulator dose, the cultivar specie, the cutting period, the substrate and the stem type, among other factors. Regulators, such as indole butyric acid (IBA) have been used and studied in olive trees, in general in hydroalcoholic concentrated solutions. The objective of this study was to evaluate the rooting in cuttings of four olive cultivars (Arbequina, Arbosana, Frantoio e Koroneiki) immersed in different periods (1, 2, 4 and 8 hours) in low concentration of (IBA) solution (300 mg L-1) diluted in only 10% of alcohol 90 oGL and absence of regulator (witness). The experimental lining used was in randomly selected blocks, arranged in factorial scheme 4 x 5 with four repetitions and 12 cuttings in each portion. The cuttings were placed in November, in a greenhouse with intermittent nebulization system, with irrigation every each minute, lasting for 10 seconds. The semi-hardwood cutting plantation, with 12 centimeters and two pairs of leafs was done in tubs of 140 cmwith carbonized rice husk substrate. The critical leaf fall occurs after the third week of the cutting placement, beginning the death after four weeks, in rates that vary according to the cultivar and the time treatment with IBA. The leaf retention, the survival and the olives stem’s rooting were negatively affected by the increasing immersion time. The 1-hour immersion treatment with IBA is effective in the cutting rooting stimulation of Arbosana (66,7%). The cultivars Koroneiki and Arbequina show low or no rooting either using IBA or not.